Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species - Qi, Mujie; Li, Houhun (Zootaxa, 2019)
The species of the genus Fujimacia Marumo, 1939 are revised from China. Among them, F. cornutiprocera Qi & Li, sp. nov., F. dayaoensis Qi & Li, sp. nov., F. gracilenta Qi & Li, sp. nov. and F. longispinosa Qi & Li, sp. nov. are described as new to science. Illustrations of adults and genitalia are provided along with keys to the Fujimacia species in China.